Administration strategy of energy management in smart grid: system view and optimization path - Liu, Peng; Wang, Siyan; Wei, Youman (Frontiers in Energy Research, 2023)
Compared with traditional grid, smart grid has been widely recognized by users for its high efficiency, energy saving and intelligent characteristics. However, with the complex-ity and diversity of smart grid ecology (new Distributed Generations types increase), how to solve the problem of power system operation imbalance caused by unstable energy has aroused people's attention. Power generation and transmission infrastructure is vulnera-ble to the interaction of various Distributed Generations (DG), which leads to the imbal-ance of power system operation, frequent voltage drops or spikes, and even power outages. This phenomenon not only wastes energy, but also affects grid security. Imbalances be-tween the supply and the consumption is the main cause of this problem. In this paper, a multi-objective optimization method based on ANFIS algorithm is proposed to solve the problems existing in the operation of Distributed Generations by improving various management schemes including control mode, inverter control, energy transfer and stor-age. And put forward reasonable suggestions for demand response, demand control and energy quality management in smart grid. Finally, the probability of power loss (LPSP) and power consumption cost were used as evaluation indexes to verify the case. The ex-perimental results show that the above algorithm determines the priority and arranges the load according to the user preference, which successfully improves the energy utilization efficiency and reduces the electricity cost. The results of the study will help build energy management systems with clear management paths and sustainability.